2018
DOI: 10.1016/j.janxdis.2018.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Ensemble machine learning prediction of posttraumatic stress disorder screening status after emergency room hospitalization

Abstract: Posttraumatic stress disorder (PTSD) develops in a substantial minority of emergency room admits. Inexpensive and accurate person-level assessment of PTSD risk after trauma exposure is a critical precursor to large-scale deployment of early interventions that may reduce individual suffering and societal costs. Toward this aim, we applied ensemble machine learning to predict PTSD screening status three months after severe injury using cost-effective and minimally invasive data. Participants (N = 271) were recru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
54
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(56 citation statements)
references
References 45 publications
2
54
0
Order By: Relevance
“…Additionally, patients' subjective and reporting biases, as well as variations in the symptoms of PTSD that can mimic other mental health conditions such as depression and anxiety, can prevent timely diagnoses. Although much work has been done on diagnosing PTSD, [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] the majority of identified indicators represent group-level risk factors (e.g., injury) with less concern for personalized predictors of PTSD (e.g., patient demographics, symptom type, and severity). 1 Recent findings suggest that PTSD is associated with an array of multimodal risk indicators, which makes it unlikely that any single vulnerability factor will account for a large amount of variance in the prediction of this complex disorder.…”
Section: Background and Significancementioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, patients' subjective and reporting biases, as well as variations in the symptoms of PTSD that can mimic other mental health conditions such as depression and anxiety, can prevent timely diagnoses. Although much work has been done on diagnosing PTSD, [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] the majority of identified indicators represent group-level risk factors (e.g., injury) with less concern for personalized predictors of PTSD (e.g., patient demographics, symptom type, and severity). 1 Recent findings suggest that PTSD is associated with an array of multimodal risk indicators, which makes it unlikely that any single vulnerability factor will account for a large amount of variance in the prediction of this complex disorder.…”
Section: Background and Significancementioning
confidence: 99%
“…The central idea behind computational methods in medical disease identification is to explore patients' data, perform feature engineering, and then use statistical or machine learning algorithms to process the data with the goal of designing a model that is able to assist clinicians in large scale and accurate disease identification. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] Intelligent assistive systems can provide details that can increase diagnostic accuracy, reduce human errors, and allow efficient use of patients' medical data. 17 Previous studies have explored different types of data sources such as EMR data 4,5 ; qualitative data including self-reported data 7 ; telephone-based and face-to-face interviews 1,8,9 ; surveys 9,10 ; scales of psychiatric symptoms 1,3,8,13 ; administrative data holdings 8,11 ; event and emergency department (ED) features 1,2,12 ; biochemical examination 8 ; injury etiology 10,12 ; sleep quality experiment, 14 and data collected using wearable devices.…”
Section: Background and Significancementioning
confidence: 99%
“…This methodological limitation can be overcome using machine learning (ML), which uses data-driven modeling to identify computational algorithms that recognize patterns and associations in complex interrelated data. To date, several studies support the promise of ML for early PTSD prognosis ( Galatzer-Levy et al, 2014 , 2017 ; Karstoft et al, 2015 ; Papini et al, 2018 ; Schultebraucks et al, 2020a ; Wshah et al, 2019 ). These studies also showed that biomedical data, including endocrine and physiological markers and received pharmacotherapy, can provide high probabilistic information in these models.…”
Section: Introductionmentioning
confidence: 99%
“…The analytical process typically involves a feature selection process, which statistically selects a number of variables from a large data set that have the greatest influence on the outcome of interest, the creation of a regression or classification algorithm, and the validation of the algorithm in an independent dataset or in an unused subset of the original data [39]. Multiple studies have used machine learning approaches to understand the development of PTSD using smartphone data [41], neuroimaging biomarkers [42], and data from longitudinal emergency room studies in adults [43,44] and children [45].…”
Section: Introductionmentioning
confidence: 99%